Deuterated carbazole derivative self-assembled monomolecular layer hole transport material and application thereof
By developing self-assembled single-layer hole transport materials based on deuterated carbazole derivatives, the problems of fewer materials and insufficient stability in existing organic solar cells are solved, and more efficient and stable photovoltaic cell performance is achieved .
Patent Information
- Application Number
- CN202411867793.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-18
AI Technical Summary
In existing organic solar cells, there are fewer types of self-assembled single-layer materials, insufficient stability, and it is difficult to meet the requirements of high efficiency and long life at the same time.
Self-assembled single-layer hole transport material based on deuterated carbazole derivatives was developed to form an ultra-thin charge-selective contact film to replace traditional charge transport materials by chemical anchoring on transparent conductive oxide electrodes.
It improves the stability and photovoltaic conversion efficiency (PCE) of organic solar cells, and exhibits better solubility and photovoltaic characteristics than traditional materials.
Smart Images

Figure BDA0005194907460000021 
Figure BDA0005194907460000031 
Figure BDA0005194907460000041
Abstract
Description
Technical Field
[0001] The present invention relates to the field of organic and perovskite solar cell interface materials and organic solar cell devices, and more specifically to deuterated carbazole derivative self-assembled monomolecular layer hole transport materials and applications thereof. Background Art
[0002] Organic solar cells are considered to be a new energy technology with great application prospects due to their outstanding advantages such as light weight, flexibility and the ability to prepare large-area devices. At the same time, organic solar cells have the potential for high conversion efficiency and low cost. Typical organic solar cells include electrodes, charge transport layers and organic light absorption layers, among which the charge transport layer is crucial to the performance and stability of the device. The charge transport layer should be as thin as possible to reduce resistance loss, and at the same time, they should cover the entire active area in a continuous and uniform manner. Traditional polymers and inorganic metal oxide materials are difficult to meet these requirements at the same time. In recent years, many research groups have proposed the use of self-assembled monolayer materials chemically anchored on transparent conductive oxide electrodes to form ultra-thin charge selective contact films to replace traditional charge transport materials. Self-assembled monolayer materials usually include three parts: hole transport end groups of aromatic amines, anchoring groups that can be chemically adsorbed on the substrate, and bridging groups between the two. This ultra-thin hole transport layer prepared based on self-assembly is conducive to the realization of high-efficiency photovoltaic devices.
[0003] At present, the highest efficiency of single-active-layer binary organic solar cell devices using self-assembled monolayer materials as hole transport layers has reached 20.50%. However, there are fewer types and the stability needs to be improved. Studies have shown that the vibration degree of the molecular bonds of deuterium-substituted materials has become smaller, which is conducive to strengthening the strength of chemical bonds, thereby greatly slowing down chemical reactions such as electrophilic substitution reactions, oxidation reactions, and proton abstraction reactions, and improving the photodegradation stability and performance of materials. Therefore, it is of great research value to develop high-efficiency deuterated self-assembled monolayer hole transport materials to improve device life and performance. Summary of the invention
[0004] In view of the current research status of self-assembled monolayer hole transport materials for organic solar cells, the present invention aims 1. to prepare four self-assembled monolayer hole transport materials (HTM) based on deuterated carbazole; and aims 2. to use the materials as hole transport interface materials in PM6:Y6 and D18:BTP-eC9 systems to prepare bulk heterojunction organic photovoltaic cell devices, thereby obtaining a method for effectively improving device stability and PCE.
[0005] The technical solution of the present invention is as follows:
[0006] A series of deuterated carbazole derivative self-assembled monolayer hole transport layer materials were synthesized, and the molecular structures are:
[0007]
[0008] Deuterated carbazole derivative self-assembled monolayer hole transport layer materials are used in organic solar cells.
[0009] Specifically: the device structure of the organic solar cell is: ITO / deuterated carbazole derivative self-assembled monolayer hole transport material / active layer / PDINO / Ag.
[0010] Furthermore, the solar cell is a binary device in which the active layer is D18:BTP-eC9 or PM6:Y6.
[0011] Furthermore, the hole transport layer prepared from the hole transport material preferably has a thickness of 10 nm.
[0012] Furthermore, the preparation conditions of the hole transport layer are as follows: dissolving the deuterated carbazole derivative self-assembled monolayer hole transport material in a mixed solvent of ethanol and dimethylformamide, and spin coating it at a speed of 2000r / min to 3000r / min in a room temperature air environment to prepare a uniform and smooth film.
[0013] Compared with the existing technology, the beneficial effects of the present invention are as follows: the synthesis method of the deuterated carbazole derivative self-assembled monolayer hole transport layer material provided by the present invention is simple; the synthesized material has good stability and solubility, and after being prepared into a heterojunction device, the photovoltaic device performance is improved compared with the photovoltaic characteristics of the hole transport layer material PEDOT:PSS. This shows that the deuterated carbazole derivative self-assembled monolayer hole transport layer material is an effective way to improve the photovoltaic performance of photovoltaic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a structural diagram of an organic solar cell device according to the present invention;
[0015] Figure 2 The molecular structures of the active layer materials PM6, Y6, D18, and BTP-ec9 in the present invention;
[0016] Figure 3 The synthetic route of DCz-C2PA, DCz-C3PA, DCz-C4PA and DCz-PhPA in the present invention is shown in FIG.
[0017] Figure 4 The current-voltage (JV) curve of the organic solar cell device based on PM6:Y6 active layer as the self-assembled monolayer hole transport layer material;
[0018] Figure 5Current-voltage (JV) curve of an organic solar cell device based on D18:BTP-ec9 active layer as a self-assembled monolayer hole transport layer material. DETAILED DESCRIPTION
[0019] The following specific examples are intended to further illustrate the present invention, but these specific embodiments do not limit the scope of protection of the present invention in any way.
[0020] Example 1
[0021] 1. Synthesis of DCz-C2PA:
[0022]
[0023] Compound 1 (700 mg, 4 mmol) was dissolved in anhydrous DMF (50 mL), and NaH (60%, 480 mg, 12 mmol) was added. After stirring for 30 minutes, 2-bromoethyl diethyl phosphate (0.87 mL, 4.8 mmol) was slowly added to the solution. The reaction was allowed to proceed overnight under nitrogen protection at room temperature. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the mixture was purified by silica gel column chromatography (eluent: dichloromethane: methanol = 20:1) to obtain a yellow solid substance, compound 2 (950 mg, 70%). 1 H NMR (400 MHz, CDCl 3 )δ4.57-4.48(t,J=7.0Hz,2H),4.05-3.94(m,4H),2.25(dp,J=7.2Hz,2H),1.27(t,J=7.0,6H).
[0024] Compound 2 (950 mg, 2.8 mmol) was dissolved in dichloromethane (30 mL), and then trimethylsilyl bromide (3.7 mL, 28 mmol) was added. After reacting for 24 h at room temperature under nitrogen atmosphere, the solvent was removed by rotary evaporation, and the crude product was dissolved in methanol (20 mL). Stirring was performed at room temperature for 4 h, and then water (20 mL) was gradually added to precipitate the product, and the solid was filtered out and washed with a mixed solvent of water and methanol (20 mL, v:v=1:1), and vacuum dried to obtain solid DCz-C2PA (510 mg). 1 H NMR (400 MHz, DMSO-d 6 )δ4.48(t,J=6.9Hz,2H),2.06(m,2H).
[0025] Example 2
[0026] The synthesis process of DCz-C3PA and DCz-C4PA refers to the synthesis of DCz-C2PA, with the only difference being that 2-bromoethyl diethyl phosphate is replaced with diethyl (3-bromopropyl) phosphonate or diethyl (4-bromobutyl) phosphonate, as shown in the attached figure.
[0027] DCz-C3PA: 1 H NMR (400 MHz, DMSO-d 6 )δ4.60(t,J=6.8Hz,2H),2.02(m,
[0028] 2H), 1.56 (m, J = 7.8 Hz, 2H).
[0029] DCz-C4PA: 1 H NMR (400 MHz, DMSO-d 6 )δ4.58(t,J=6.9Hz,2H),2.01(m,
[0030] 2H), 1.54 (m, J = 7.7 Hz, 4H).
[0031] Example 3
[0032] Synthesis of DCz-PhPA
[0033]
[0034] Compound 1 (1.75 g, 10 mmol), 1-bromo-4-iodobenzene (5.66 g, 20 mmol), cuprous iodide (0.190 g, 1 mmol), 1,2-cyclohexanediamine (0.228 g, 2 mmol) and potassium phosphate (6.37 g, 30 mmol) were dissolved in toluene (50 mL). The mixture was reacted for 12 h at 110 ° C under a nitrogen atmosphere. After the reaction, the system was extracted with dichloromethane and saturated saline solution, and the organic phases were combined and dried over anhydrous magnesium sulfate. The dried solution was rotary evaporated to remove the solvent to obtain a crude product, which was purified by silica gel column chromatography (eluent: petroleum ether: dichloromethane = 4:1) to obtain a white solid, compound 3 (2.8 g, 85%). 1 H NMR (400 MHz, CDCl 3 )δ7.9-7.88(m,2H),7.74-7.68(m,2H).
[0035] Compound 3 (1.0 g, 3 mmol), palladium acetate (16.8 mg, 0.075 mmol), 1,1'-bis(diphenylphosphino)ferrocene (83.2 mg, 0.15 mmol), potassium acetate (29.4 mg, 0.3 mmol) and triethylamine (364 mg, 3.6 mmol) were dissolved in anhydrous tetrahydrofuran (35 mL). Stirred for 15 minutes under nitrogen atmosphere at 80 °C. Diethyl phosphite (414 mg, 3 mmol) was then added and the reaction continued for 12 h. After the reaction was completed, the reaction mixture was filtered and rinsed with tetrahydrofuran, and the obtained filtrate was rotary evaporated to remove the solvent to obtain a crude product, which was purified by silica gel column chromatography (eluent: dichloromethane: methanol = 20:1) to obtain a white solid, compound 4 (0.82 g, 70%). 1 H NMR (400 MHz, CDCl 3 )δ7.98-7.91(m,2H),7.74-7.65(m,2H),4.35-4.09(m,4H),1.41(t,J=7.1Hz,6H).
[0036] Compound 4 (0.82 g, 2.1 mmol) was dissolved in dichloromethane (20 mL), and then trimethylsilyl bromide (2.8 mL, 21 mmol) was added. After reacting for 24 h at room temperature under nitrogen atmosphere, the solvent was removed by rotary evaporation, and the crude product was dissolved in methanol (15 mL). Stirring was performed at room temperature for 4 h, and then water (15 mL) was gradually added to precipitate the product. The solid was filtered out, washed with a mixed solvent of water and methanol (20 mL, v:v=1:1), and vacuum dried to obtain solid DCz-PhPA (450 mg). 1 HNMR (400 MHz, DMSO-d 6 )δ8.01-7.90(m,4H).).
[0037] Comparative Example 1
[0038] The device structure of the organic solar cell based on the comparative hole transport material PEDOT:PSS is: ITO / PEDOT:PSS / active layer / PDINO / Ag. The mass ratio of PM6:Y6 in the active layer is 1:1.2. Its production scheme is as follows:
[0039] Cleaning and pretreatment of ITO substrates
[0040] The ITO substrate was cleaned in an ultrasonic cleaner in the order of washing liquid (10 min), isopropanol (20 min), acetone (20 min), deionized water (10 min×4), and isopropanol (20 min), and dried in an oven overnight. Before use, the ITO surface was treated with UV ozone for 15 min and cooled to room temperature.
[0041] Spin coating of hole transport layer PEDOT:PSS
[0042] The PEDOT:PSS solution was spin-coated at 2500 r / min for 30 s in a room temperature air environment, then baked at 100°C for 15 min, and then cooled at room temperature for 15 min to prepare a uniform and smooth film (30 nm thick).
[0043] Mixing and spin coating of active layer materials
[0044] In a glove box with a nitrogen atmosphere, PM6:Y6 with a mass ratio of 1:1.2 and a donor concentration of 10 mg / mL was dissolved in chloroform and spin-coated at 2500 r / min for 30 s. After that, it was annealed at different temperatures for 10 min and then cooled at room temperature for 20 min to form a uniform and smooth film (thickness of 100 nm).
[0045] Spin coating of electron transport layer PDINO and evaporation of cathode Ag
[0046] In a glove box with a nitrogen atmosphere, PDINO with a concentration of 1 mg / mL was spin-coated at a speed of 3000 r / min for 30 s to prepare a uniform and smooth film (thickness of 10 nm). The spin-coated device was then placed in a vacuum evaporation chamber at 1×10 -5 A 100nm thick metal electrode Ag was evaporated on the active layer under Pa.
[0047] Device performance test
[0048] Under standard test conditions (AM1.5, 100mW / cm 2 ), and measure the device’s V oc =0.832V, J sc =26.04mA / cm 2 , FF=74.64%, PCE=16.19%.
[0049] Example 4
[0050] Organic solar cell device based on self-assembled monolayer hole transport material of deuterated carbazole prepared in Example 1, Example 2 and Example 3:
[0051] The device structure of the organic solar cell is: ITO / deuterated carbazole derivative self-assembled monolayer hole transport material / active layer / PDINO / Ag. The mass ratio of PM6:Y6 in the active layer is 1:1.2. The production scheme is as follows:
[0052] Cleaning and pretreatment of ITO substrate:
[0053] The ITO substrate was cleaned in an ultrasonic cleaner in the order of washing liquid (10 min), isopropanol (20 min), acetone (20 min), deionized water (10 min×4), and isopropanol (20 min), and dried in an oven overnight. Before use, the ITO surface was treated with UV ozone for 15 min and cooled to room temperature.
[0054] Spin coating of self-assembled monolayer hole transport materials of deuterated carbazole derivatives:
[0055] A 0.9 mg / mL mixed solution of ethanol and dimethylformamide (volume ratio 10:1) of a deuterated carbazole derivative self-assembled monolayer hole transport material was spin-coated at 2500 r / min for 30 s in an air environment at room temperature to prepare a uniform and smooth film with a thickness of 10 nm.
[0056] Mixing and spin coating of active layer materials:
[0057] In a glove box with a nitrogen atmosphere, PM6:Y6 with a mass ratio of 1:1.2 and a donor concentration of 10 mg / mL was dissolved in chloroform and spin-coated at 2500 r / min for 30 s. After that, it was annealed at different temperatures for 10 min and then cooled at room temperature for 20 min to form a uniform and smooth film (thickness of 100 nm).
[0058] Spin coating of electron transport layer PDINO and evaporation of cathode Ag:
[0059] In a glove box with a nitrogen atmosphere, PDINO with a concentration of 1 mg / mL was spin-coated at a speed of 3000 r / min for 30 s to prepare a uniform and smooth film (thickness of 10 nm). The spin-coated device was then placed in a vacuum evaporation chamber at 1×10 -5 A 100nm thick metal electrode Ag was evaporated on the active layer under Pa.
[0060] Device performance test:
[0061] Under standard test conditions (AM1.5, 100mW / cm 2 ), based on the DCz-C4PA deuterated carbazole derivative self-assembled monolayer hole transport material device, the performance was measured to be V oc =0.861V, J sc =26.51mA / cm 2 , FF=77.40%, PCE=17.57%.
[0062] Example 5
[0063] Organic solar cell device based on the self-assembled monolayer hole transport material DCz-C4PA based on deuterated carbazole prepared in Example 2:
[0064] The device structure of the organic solar cell is: ITO / DCz-C4PA / active layer / PDINO / Ag. The mass ratio of the active layer D18:BTP-eC9 is 1:1.2. The production scheme is as follows:
[0065] Cleaning and pretreatment of ITO substrates
[0066] The ITO substrate was cleaned in an ultrasonic cleaner in the order of washing liquid (10 min), isopropanol (20 min), acetone (20 min), deionized water (10 min×4), and isopropanol (20 min), and dried in an oven overnight. Before use, the ITO surface was treated with UV ozone for 15 min and cooled to room temperature.
[0067] Spin coating of self-assembled monolayers of deuterated carbazole derivatives as hole transport materials
[0068] A mixed solution of 0.9 mg / mL DCz-C4PA in ethanol and dimethylformamide (volume ratio 10:1) was spin-coated at 2500 r / min for 30 s in an air environment at room temperature to prepare a uniform and smooth film.
[0069] Mixing and spin coating of active layer materials
[0070] In a glove box with a nitrogen atmosphere, D18:BTP-eC9 was dissolved in chloroform with a mass ratio of 1:1.2 and a donor concentration of 10 mg / mL, and spin-coated at 2500 r / min for 30 s. It was then annealed at different temperatures for 10 min and subsequently cooled at room temperature for 20 min to form a uniform and smooth film.
[0071] Spin coating of electron transport layer PDINO and evaporation of cathode Ag
[0072] In a glove box with a nitrogen atmosphere, PDINO with a concentration of 1 mg / mL was spin-coated at a speed of 3000 r / min for 30 s to prepare a uniform and smooth film. The spin-coated device was then placed in a vacuum evaporation chamber at 1×10 -5 A 100nm thick metal electrode Ag was evaporated on the active layer under Pa.
[0073] Device performance test
[0074] Under standard test conditions (AM1.5, 100mW / cm 2 ), and measure the device’s V oc =0.871V, J sc =27.82mA / cm 2 , FF=77.10%, PCE=18.68%.
[0075] Table 1. Performance parameters of self-assembled monolayer hole transport layer materials of different deuterated carbazole derivatives based on PM6:Y6 devices
[0076]
[0077] Table 2. Performance parameters of D18:BTP-ec9 device based on DCz-C4PA self-assembled monolayer hole transport layer material
[0078]
[0079] Although the present invention has been described in conjunction with the preferred embodiments, the present invention is not limited to the above embodiments, and it should be understood that the appended claims summarize the scope of the present invention. Under the guidance of the inventive concept, those skilled in the art should be aware that certain changes made to the various embodiments of the present invention will be covered by the spirit and scope of the claims of the present invention.
Claims
1. A self-assembled monolayer hole transport material based on deuterated carbazole, characterized in that: The chemical structure of the self-assembled monolayer hole transport material based on deuterated carbazole is:
2. An application of the self-assembled monolayer hole transport material based on deuterated carbazole as claimed in claim 1, characterized in that: The self-assembled monomolecular layer hole transport material of deuterated carbazole is prepared into a hole transport layer and applied to an organic solar cell or a perovskite solar cell.
3. The use according to claim 2, characterized in that: The solar cell device structure is ITO / deuterated carbazole derivative self-assembled monolayer hole transport material / active layer / PDINO / Ag.
4. The use according to claim 3, characterized in that: The solar cell is a binary device with an active layer of D18:BTP-eC9 or PM6:Y6.
Citation Information
Patent Citations
Non-fullerene acceptor material and preparation method and application thereof
CN116375732A
Self-assembled monomolecular layer material based on conjugated linking group, preparation method thereof and solar cell
CN117659083A
Application of asymmetric thiophene solution additive in organic solar cell
CN117939896A
Perovskite / organic laminated solar cell based on thiocyanate micromolecule salt and preparation method of perovskite / organic laminated solar cell
CN118284280A
Fluoroalkyl chain-containing non-fullerene receptor as well as preparation method and application thereof
CN118480057A